Tadeusz Stryjakiewicz Tomasz Kaczmarek Michał Męczyński Jerzy J. Parysek Krzysztof Stachowiak Policies and strategies in Poznan. How to enhance the city’s competitiveness. ACRE report 10.8 - Czasopisma, Redakcja (Rozwój Regionalny i Polityka Regionalna, 2010)
Tadeusz Stryjakiewicz Tomasz Kaczmarek Michał Męczyński Jerzy J. Parysek Krzysztof Stachowiak Policies and strategies in Poznan. How to enhance the city’s competitiveness. ACRE report 10.8 University of Amsterdam, 2010 ISBN 978-94-90312-32-9